A Guideline for Undergraduate Students at the College of Music, Mahasarakham University to Develop Advanced Solo in Folk Music Skills - Sarawut Choatchamrat; Akapong Phulaiyaw; Thanyalak Moonsuwan; Awirut Thotham; Sayam Chuangprakhon; Rukbancha Phimprajun (Journal of Educational Issues, 2024)
The high-class performance style of Isan folk music is to perform as a soloist with techniques, methods, tactics, essence, rhythm, and postures. There are melodious, fun and fully indicate the ability of the performer, composer, and combiner of the music. This research aims to study the pattern of Isan folk as a solo and also creative process. Data collections are documents and field study methods—observation, interview of six gurus or scholars, five of folk music teachers, eight of folk music soloists, eight of folk music performers, and thirty members of the general public. The research results were presented by analytical description. The results are that, the advance of folk music solo happens by learning the principles and concepts of solo performance management. Demonstration of advanced folk instrument practice skills and solo performances in the practice of advanced folk instruments are shown the concepts that create works of skill in performing solo performances of Isan folk music. The style is a solo performance of Isan folk music, with techniques, methods, tactics, and rhythmic styles and the main pattern melodies in Isan folk music convey the melodious and fun character according to the traditional style of the local area. There are guidelines for playing each Isan folk instrument along with the creative process that combines contemporary folk music. There are various styles of melodies, and movement patterns, such as slow rhythms, medium rhythms, fast rhythms, etc. Summarizing the format and creative process of solo music, Isan folk music is an advanced creation of folk music with the idea of creating according to the traditional style of the Isan region and also incorporating contemporary Isan folk music. It conveys the skill of the performers who perform folk music solos to achieve a melodic sound, fun for the audience.